Blocking by fixed and variable stimuli: effects of stimulus distribution on blocking - Jennings, Dómhnall J.; Bonardi, Charlotte (Taylor & Francis, 2016)
An experiment with rats compared the ability of fixed and variable duration cues to produce blocking. Rats in Group B (Blocking) were trained that both fixed- (F) and variable- (V) duration cues would be followed by food delivery. In a subsequent training stage F and V continued to be reinforced, but F was accompanied by X, and V by Y. In the test phase responding to X and Y was examined. Control Group O (Overshadowing) received identical treatment, except that F and V were nonreinforced in the first training stage. In Group B there was evidence for blocking, but only of X which had been conditioned in compound with the fixed-duration F; there was no evidence for blocking of Y, which had been conditioned in compound with the variable duration V. It is suggested that this result may occur because fixed cues reach a higher, more stable asymptote of associative strength than their variable equivalents.